PERLINDUNGAN HUKUM KONSUMEN BAGI PELANGGAN AIR MINUM DI KOTA BEKASI - Noor Hidayati (Universitas Bina Sarana Informatika, 2012)
This research aims to discuss the implementation of Consumer’s Right Protection (UUPK) of drinking water customers in the city of Bekasi period 2010. Form of research is done is by using a normative juridical secondary data. Secondary data obtained through interviews, while through the research literature that comes from certain documents and materials. The research data when analyzed using qualitative methods obtained results that the rights of consumers that are set in the UUPK has not fully met by Bekasi City PDAM (PDMA) as business actor. On the other side involvement of district attorney in collection of accounts receivable, Attorney taps through a special power of attorney from the taps to the Attorney helps increase income taps, and increase business profitability of PDAM. Therefore, the PDAM should improve the quality of drinking water services to customers continuously in accordance with the standards set so that the rights of consumers can be met according to UUPK. And the municipal government should make regulations governing the area of responsibility as entrepreneurs PDAM water provider for the needs of the community, so if there are omissions or errors in service, customers know their rights. Because it needs a commitment from the PDAM to improve the quality of public services in a professional manner. Keywords: Legal protection, Consumer